Understanding basic chemistry through problem solving : the learner's approach - Chan, Kim Seng; Tan, Jeanne (Singapore : World Scientific, WSeducation, 2015)
The particulate nature of matter -- Atomic structure -- Chemical bonding -- Mole concept, formula, and stoichiometry -- Energy changes and fuels -- Rate of chemical reactions -- Equilibria, ammonia, and sulfur -- Acids, bases, and salts -- Redox reactions -- Electric cells and the reactivity series -- Electrolysis -- The periodic table -- Metals and extraction -- Air and the environment -- Organic chemistry -- Experimental chemistry.
including index.
Keywords: Chemistry -- Textbooks -- United kingdom; Chemistry -- Textbooks; Chemistry -- Examinations, questions, etc -- Study guides -- Great Britain; Chemistry -- Examinations, questions, etc. -- Study guides